The Objective Measurement of Movement vs the Intensification of ADHD Symptoms in Assessment of Parents and Doctors - Dabkowska, Małgorzata; Pracki, Tadeusz; Pracka, Daria (Medical and Biological Sciences, 2012)
The purpose of this work was the objective actigraphic evaluation of movement at children with ADHD (Attention Deficit Hyperactivity Disorder) in relation to the evaluation of symptom intensification according to their parents (ADHD-RS IV) and a medical qualification to a subtype of ADHD (DSM IV TR). The motor activity of a child was evaluated by means of an actigraph - Actiwatch 4 produced by Cambridge Neurotechnology Ltd. The investigated group consisted of 37 children (32 boys, 5 girls). Results: there were no differences in the activity between the group of children with recognized ADHD combined subtype and the group of children with recognized ADHD predominantly inattentive subtype observed. More serious attention disorders occur in case of children, who in later hours of the day have the maximum activity intensity. The scores of items evaluating the hyperactivity and impulsiveness did not correlate with the results of activity measurement. The results of actigraphic measurement did not correlate with the evaluation of the activity intensification according to parents.